Etika penggunaan AI dalam Karya : Pengabdian Masyarakat kepada Komunitas Film linkpictureID di Depok Jawa Barat - Ahmad Zakki Abdullah; I Nyoman Aji Suadhana Rai; Abdul Ghofur; Azwar Azwar (Universitas 45 Surabaya, 2024)
The use of AI (artificial intelligence) in a work in the film community is growing very rapidly. The LinkpictureID film community is one of them. Applications that use AI are increasingly being used by the film community. This has a quite important impact considering that there are many things that can be used in the use of AI in a film where it must apply in accordance with the ethical rules that apply in society. The use of AI in accordance with ethical rules in society is formed based on norms. On this occasion, we help the LinkpictureID film community to be able to utilize AI in accordance with applicable norms such as interactive dialogues, the formation of FGDs and presentations by experts in the use of AI in a work. As a result of the service, it is hoped that the creative industries can utilize AI in accordance with the interests of policy makers so that they do not deviate from the norms that apply in the community of Depok, West Java.